2018
DOI: 10.1002/adfm.201707309
|View full text |Cite
|
Sign up to set email alerts
|

DNA Origami‐Guided Assembly of the Roundest 60–100 nm Gold Nanospheres into Plasmonic Metamolecules

Abstract: DNA origami can provide programmed information to guide the selfassembly of gold nanospheres (Au NSs) into higher-order supracolloids. Molecularly precise and truly 2D/3D integration of Au NSs is possible using DNA origami-enabled assembly, and the resulting assemblies have potential applications in plasmonics and metamaterials. However, the relatively small size (<60 nm) and randomly faceted Au NSs that have been used thus far in DNA origami-enabled assembly have limited their nanophotonic applications. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 47 publications
1
53
0
3
Order By: Relevance
“…Second, it employs colloidal MNPs, which are less prone to surface defects and can be fabricated with higher uniformity than evaporated metallic structures leading to improved reproducibility and performance. 65 Finally, with this technique, a single-photon emitter can be routinely placed in the hotspots of MNPs with nanometer precision, a key factor in controlling the coupling between single molecules and nanocavities. 66,67 These advantages were initially exploited to revisit experiments on uorescence-enhanced spectroscopy 68,69 and SERS [70][71][72] using dimer nanocavities made of Au or Ag, achieving enhancement values outperforming in some cases those obtained by using nanocavities fabricated with more complex top-down lithographic techniques.…”
Section: From Nano To Picocavities For High-resolution Single-moleculmentioning
confidence: 99%
“…Second, it employs colloidal MNPs, which are less prone to surface defects and can be fabricated with higher uniformity than evaporated metallic structures leading to improved reproducibility and performance. 65 Finally, with this technique, a single-photon emitter can be routinely placed in the hotspots of MNPs with nanometer precision, a key factor in controlling the coupling between single molecules and nanocavities. 66,67 These advantages were initially exploited to revisit experiments on uorescence-enhanced spectroscopy 68,69 and SERS [70][71][72] using dimer nanocavities made of Au or Ag, achieving enhancement values outperforming in some cases those obtained by using nanocavities fabricated with more complex top-down lithographic techniques.…”
Section: From Nano To Picocavities For High-resolution Single-moleculmentioning
confidence: 99%
“…In contrast, bottom-up methods based on chemical assembly offer a cheap, fast and exible technology for preparing close-packed colloidal particles as LSPR substrate. [34][35][36] Guillermo et al found that laser irradiation at high energy produced a near-eld enhancement at the interparticle gaps, causing the local temperature to increase high enough to melt the tip of the gold nanorod. 36 This further proves that the coupling effect brought by the gap between the particles can enhance its photothermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, various 2D and 3D plasmonic metamolecules and optical antennas can be developed by AFM assembly . Recent advances in a chemical route for the synthesis of the roundest AuNPs have further improved the accuracy (a resolution of a few nanometers) and reliability of this AFM assembly method . Benefitting from this technological advance in AFM assembly, 32 roundest 60 nm Au nanospheres (NSs) were individually positioned at differently programmed locations.…”
Section: Photochromic‐isomerization‐induced Directional Mass Migratimentioning
confidence: 99%